Prevalence of Spontaneous Bacterial Peritonitis in Patients Presenting with Upper Gastrointestinal Bleeding in Decompensated Chronic Liver Disease Patients - Liaqat Ali, Muhammad Naeem, Muhammad Imran Ullah, Mujahid Aslam, Hamid Ullah, Abbas Masood, Assad Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Over the last several decades, chronic liver disease incidence has increased globally. One of the most common complications of cirrhosis is spontaneous bacterial peritonitis. Objective: To assess the prevalence of spontaneous bacterial peritonitis in patients presenting with upper gastrointestinal bleeding in decompensated chronic liver disease patients Methodology: The current study was cross sectional carried out at the Gastroenterology department, Qazi Hussain Ahmad Medical Complex, Nowshera. The duration of study was one year from August 2021 to August 2022. All the data like name, age gender and other information related to medical history were recorded on a predesigned proforma. All the analysis of collected data was done by employing IBM SPSS version 24. . Results: In the current study, totally 100 patients were enrolled. There were 60 (60%) male participants and 40 (40%) patients were female in our study. The overall prevalence of spontaneous bacterial peritonitis in patients presenting with upper gastrointestinal bleeding in decompensated chronic liver disease was 29 (29%). Conclusion: Our study concludes that the prevalence of spontaneous bacterial peritonitis in patients presenting with upper gastrointestinal bleeding in decompensated chronic liver disease patients is high. Spontaneous bacterial peritonitis frequency is also high in patients with Child-Pugh Class C as compared to Child-Pugh Class B. Keywords: Decompensated chronic liver disease; spontaneous bacterial peritonitis; Prevalence